CircPRMT5, a Potential Salivary Biomarker, Facilitates the Progression of Head and Neck Squamous Cell Carcinoma via the IGF2BP3-SERPINE1 Pathway - Jiang S; Ou L; Wang Y; Su K; Chen Z; He L; Xu X; Cheng B; Xia J; Fan Z (International Journal of Nanomedicine)
Siqi Jiang,1,2 Linlin Ou,1,2 Yueqi Wang,1,2 Kai Su,1,2 Zhipei Chen,1,2 Lihong He,1,2 Xun Xu,1,2 Bin Cheng,1,2 Juan Xia,1,2 Zhaona Fan1,2 1Hospital of Stomatology, Sun Yat-sen University, Guangzhou, People’s Republic of China; 2Guangdong Provincial Key Laboratory of Stomatology, Guanghua School of Stomatology, Sun Yat-sen University, Guangzhou, People’s Republic of ChinaCorrespondence: Zhaona Fan; Juan Xia, Hospital of Stomatology, Sun Yat-sen University, No. 56 Lingyuanxi Road, Guangzhou, Guangdong, 510055, People’s Republic of China, Tel +86 20 87394123 ; +86 20 83741891, Fax +86 20 83822807, Email fanzhn3@mail.sysu.edu.cn; xiajuan@mail.sysu.edu.cnPurpose: Circular RNAs (circRNAs) are associated with the progression of tumors and hold promise as potential biomarkers for liquid biopsy. Among these, the role of circPRMT5 in head and neck squamous cell carcinoma (HNSCC) remains to be elucidated. This study aims to examine the role and underlying mechanisms of circPRMT5 in the progression of HNSCC and to assess its potential diagnostic value in saliva exosomes.Methods: The expression of circPRMT5 and its clinical significance in HNSCC were investigated. Both in vitro and in vivo studies were performed to elucidate the biological role of circPRMT5 in HNSCC. RNA sequencing was utilized to identify downstream mechanisms. To evaluate and validate these mechanisms, Western blotting, RNA-FISH, immunofluorescence, immunohistochemistry, RIP, and rescue experiments were employed. Finally, salivary exosomes were isolated, and the expression levels of circPRMT5 were assessed using qRT-PCR.Results: The upregulation of circPRMT5 in HNSCC tissues was identified to be correlated with cervical lymph node metastasis and advanced clinical T stage. Both in vitro and in vivo experiments manifested that circPRMT5 promoted the proliferation and metastasis of HNSCC. Mechanistically, circPRMT5 was demonstrated to directly bind to and stabilize the insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3), which, subsequently, binds to and stabilizes the serpin family E member 1 (SERPINE1) mRNA, thereby enhancing SERPINE1 expression. Furthermore, rescue experiments indicated that the proliferative, invasive, and migratory effects of circPRMT5 in HNSCC were dependent on the involvement of IGF2BP3 and SERPINE1. Notably, circPRMT5 levels were significantly elevated in the saliva exosomes of HNSCC patients, exhibiting substantial diagnostic value.Conclusion: CircPRMT5 exhibits significant diagnostic utility through salivary exosomes and plays a crucial role in promoting the progression of HNSCC via the IGF2BP3-SERPINE1 pathway. These findings highlight the potential of circPRMT5 as a noninvasive diagnostic biomarker and a therapeutic target for patients with HNSCC. Keywords: head and neck cancer, circPRMT5, IGF2BP3, SERPINE1, salivary exosomes